Raman and IR spectroscopic characterization of molybdenum disulfide under quasi‐hydrostatic and non‐hydrostatic conditions. Issue 6 (3rd March 2017) - Shen, Pengfei; Li, Quanjun; Zhang, Huafang; Liu, Ran; Liu, Bo; Yang, Xigui; Dong, Qing; Cui, Tian; Liu, Bingbing
Abstract : Layered transition‐metal dichalcogenides (TMDs) have recently attracted intense scientific and engineering interest because of their unique semiconducting and opto‐electronic properties. We investigated the pressure‐induced structural phase transition of layered semiconductor molybdenum disulfide (MoS2 ) using Raman spectroscopy and studied its metallization using infrared (IR) spectroscopy under both non‐hydrostatic and quasi‐hydrostatic conditions. Under quasi‐hydrostatic and non‐hydrostatic conditions, we found that the structural phase transition from 2 H c stacking to 2 H a stacking starts at approximately 16 and 21 GPa, respectively, and finishes at ∼35 and ∼41 GPa, respectively. Furthermore, the structural phase transition was followed by a semiconductor‐to‐metal (S‐M) electronic transition. The pressure point of metallization under quasi‐hydrostatic conditions is ∼5 GPa lower than that under non‐hydrostatic conditions.